Prejudice in Swiss Naturalization Decisions: Theory and Evidence - Dragan Ilic (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Recent empirical studies have revealed prejudice based on country of origin in the Swiss naturalization system before courts banned closed ballot voting in 2003. Although the switch to elected councils has ameliorated the situation for the discriminated applicant groups, little has been known about the issue since due to lack of microlevel data. This paper presents an alternative approach. I propose a simple model of a council deciding whether to grant applicants citizenships. The model implies an outcome test for relative prejudice using rejection rates grouped by country of origin. Importantly, this specific outcome test does not suffer from the well-known infra-marginality problem. The test is implemented with unique data from 2003 to 2012 raised from large Swiss municipalities to test the hypothesis of no relative prejudice.
Keywords: J71; K42; J70; 330